A New Crystal Phase Molybdate Yb2Mo4O15: The Synthesis and Upconversion Properties - Wang, Hai-Qiao; Mackovic, Mirza; Osvet, Andres; Litzov, Ivan; Epelbaum, Elena; Stiegelschmitt, Alfons; Batentschuk, Miroslaw; Spiecker, Erdmann; Brabec, Christoph (Particle & Particle Systems Characterization, 2015)
A new upconversion nanocrystal phase Yb2Mo4O15:Er is developed by using a facile aqueous-precipitation procedure combined with thermal annealing. Nanocrystals of Yb2Mo4O15 are exclusively synthesized, with particle sizes ranging from 1 to 20 nm. The optical properties are characterized and a high upconversion quantum yield is determined to be approximate to 1.3% at room temperature, under excitation of approximate to 500 mW cm(-2) IR (975 nm). To the best of our knowledge, this is the first work concerning the synthesis of nanocrystalline Yb2Mo4O15 and the characterization of its upconversion properties, which possesses the potential to be utilized in bio-probing and thin-film optoelectronic device applications.
Keywords: upconversion; Yb2Mo4O15:Er; nanocrystals; characterization

Dielectric Data of Ceramic Substrates at High Frequencies - Stiegelschmitt, Alfons; Roosen, Andreas; Ziegler, Christof; Martius, Siegfried; Schmidt, Lorenz-Peter (Journal of the European Ceramic Society, 2004)
UnivIS-Import:2015-03-09:Pub.2004.tech.IE.LEH.dielec

Eu2+ and Eu3+ based "concentrated phosphors" as converters for UV LED light: two approaches and two new examples - Batentschuk, Miroslaw; Geisler, R.; Hum, Jasmin; Iqbal, Farasat; Meister, Frank; Osvet, Andres; Stiegelschmitt, Alfons; Winnacker, Albrecht (Applied Physics B-Lasers and Optics, 2012)
The absolute majority of phosphors are composed of a host lattice and some percentage of an activator. At higher activator concentrations the concentration quenching occurs. However, there are phosphors in which only minor quenching of the emission occurs with increasing of the activator content. Based on the existence of two different valence states of the Eu ion (2+ and 3+), two approaches for the development of "concentrated phosphors", i.e. light emitting materials in which the activator ion is a main part of the crystal lattice, are discussed. In both approaches, reduced energy migration leading to the luminescence quenching is considered as a main condition to reach a high quantum efficiency of a concentrated phosphor. Two kinds of phosphors-Eu2+-doped alumosilicate and Eu3+-doped oxyfluoride-are used as an experimental basis for this discussion. Starting from the stoichiometric Ca1-x Eu-x(2+) A1(2)si(2)O8 anorthite and Eu3+OF oxyfluorides, the non-stoichiometric powders with Eu-0.92(2+) A1(1.76)Si(2.24)O(8), Eu3+(O, F)(2,35) and Eu3+(O, F)(2,16) compositions were synthesized by a solid state reaction and investigated. It was shown that-in spite of the almost 100% Eu concentration-light converters with high quantum efficiency of more than 45% can be realized. A possible application of these materials as UV LED light converters for white light emitting diodes are discussed as well.

Hypericin-bearing magnetic iron oxide nanoparticles for selective drug delivery in photodynamic therapy - Unterweger, Harald; Subatzus, Daniel; Tietze, Rainer; Janko, Christina; Poettler, Marina; Stiegelschmitt, Alfons; Schuster, Matthias; Maake, Caroline; Boccaccini, Aldo R.; Alexiou, Christoph (International Journal of Nanomedicine, 2015)
Combining the concept of magnetic drug targeting and photodynamic therapy is a promising approach for the treatment of cancer. A high selectivity as well as significant fewer side effects can be achieved by this method, since the therapeutic treatment only takes place in the area where accumulation of the particles by an external electromagnet and radiation by a laser system overlap. In this article, a novel hypericin-bearing drug delivery system has been developed by synthesis of superparamagnetic iron oxide nanoparticles (SPIONs) with a hypericin-linked functionalized dextran coating. For that, sterically stabilized dextran-coated SPIONs were produced by coprecipitation and crosslinking with epichlorohydrin to enhance stability. Carboxymethylation of the dextran shell provided a functionalized platform for linking hypericin via glutaraldehyde. Particle sizes obtained by dynamic light scattering were in a range of 55-85 nm, whereas investigation of single magnetite or maghemite particle diameter was performed by transmission electron microscopy and X-ray diffraction and resulted in approximately 4.5-5.0 nm. Surface chemistry of those particles was evaluated by Fourier transform infrared spectroscopy and ζ potential measurements, indicating successful functionalization and dispersal stabilization due to a mixture of steric and electrostatic repulsion. Flow cytometry revealed no toxicity of pure nanoparticles as well as hypericin without exposure to light on Jurkat T-cells, whereas the combination of hypericin, alone or loaded on particles, with light-induced cell death in a concentration and exposure time-dependent manner due to the generation of reactive oxygen species. In conclusion, the combination of SPIONs’ targeting abilities with hypericin’s phototoxic properties represents a promising approach for merging magnetic drug targeting with photodynamic therapy for the treatment of cancer.
Keywords: Hypericin; Magnetic drug targeting; Photodynamic therapy; SPION